Mandibular angle morphology in open bite subjects according to the skeletal relationship: a cbct short report - Gina Laquihuanaco; Yalil Rodríguez-Cárdenas; Gustavo Ruíz-Mora; Abraham Meneses-López; Luis Arriola-Guillén (Universidad de Concepción., 2022)
Aim: The purpose of this research was to three-dimensionally evaluate the mandibular angle morphology in open bite subjects with different sagittal skeletal relationships. Material and Methods: Cone beam computed tomography (CBCT) images of 26 subjects (12 men and 14 women) with anterior open bite were evaluated. The sample included 3 groups categorized by their sagittal skeletal relationship (based on ANB angle and anteroposterior dysplasia indicator (APDI)): Class I (n=9), Class II (n=6) and Class III (n=11). The total gonial angle, upper gonial angle, lower gonial angle, intergonial width, interantegonial width and antegonial notch depth were measured. ANOVA and Tukey tests were used for intergroup comparison. The Kruskal Wallis test was also used when necessary. In addition, the Pearson correlation coefficient was calculated to evaluate significant correlations between overbite and antegonial notch depth with gonial angle, Frankfurt mandibular plane angle (FMA) and the palatal plane-mandibular plane (PP-MP). Results: A significant difference was only found on the upper gonial angle between Class II and Class III (p=0.047). The upper gonial angle showed greater values (48°±3°) with the mandibular branch toward backward in Class III subjects and lower values (42.42°±4.39°) with the mandibular ramus leaning forward in subjects with Class II skeletal relationship. Besides, only a statistically significant correlation was found between overbite and the lower gonial angle (r=-0.418, p=0.034). Conclusion: Mandibular angle morphology is similar in anterior open bite subjects with different sagittal skeletal relationships, except for the upper gonial angle which is increased in Class III and decreased in Class II subjects with open bite. Lower gonial angle is negatively correlated with overbite. This difference should be considered by orthodontists when planning their treatments.